Nasogastric Nutrition versus Nasojejunal Nutrition in Patients with Severe Acute Pancreatitis: A Meta-Analysis of Randomized Controlled Trials - Youfeng Zhu; Haiyan Yin; Rui Zhang; Xiaoling Ye; Jianrui Wei (Gastroenterology Research and Practice)
Introduction. Previous studies have shown that the nasogastric (NG) route seems equivalent to the nasojejunal (NJ) route in patients with severe acute pancreatitis (SAP). However, these studies used a small sample size and old criteria for diagnosing SAP, which may include some patients with moderate SAP, according to the newly established SAP criteria (Atlanta 2012 classification). Based on the changes in the criteria for classifying SAP, we performed an up-to-date meta-analysis. Method. We reviewed the PubMed, EMbase, China National Knowledge Infrastructure, Wanfang Database, and Cochrane Central Register of Controlled Trials electronic databases. We included randomized controlled trials comparing NG and NJ nutrition in patients with SAP. We performed the meta-analysis using the Cochrane Collaborations’ RevMan 5.3 software. Results. We included four randomized controlled trials involving 237 patients with SAP. There were no significant differences in the incidence of mortality, infectious complications, digestive complications, achievement of energy balance, or length of hospital stay between the NG and NJ nutrition groups. Conclusions. NG nutrition was as safe and effective as NJ nutrition in patients with SAP. Further studies are needed to confirm our results.